2010
DOI: 10.1016/j.jecp.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for knowledge of the syntax of large numbers in preschoolers

Abstract: a b s t r a c tThe aim of this study was to provide evidence for knowledge of the syntax governing the verbal form of large numbers in preschoolers long before they are able to count up to these numbers. We reasoned that if such knowledge exists, it should facilitate the maintenance in short-term memory of lists of lexical primitives that constitute a number (e.g., three hundred forty five) compared with lists containing the same primitives but in a scrambled order (e.g., five three forty hundred). The two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…Despite preschoolers' limited knowledge of the number list, the current study indicates that preschoolers show superior recall performance for lists of lexical primitives in a conventional order as compared to a scrambled order. This result supports and extends previous data reported by Barrouillet et al (2010). In their study, preschool children showed increased recall performance for auditory lists of large numbers (e.g., three ninety hundred two) when the numbers form a syntactically coherent structure allowing regrouping of the numbers in a single large number chunk (e.g., three hundred ninety two), although children of this age cannot yet count up to such large numbers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite preschoolers' limited knowledge of the number list, the current study indicates that preschoolers show superior recall performance for lists of lexical primitives in a conventional order as compared to a scrambled order. This result supports and extends previous data reported by Barrouillet et al (2010). In their study, preschool children showed increased recall performance for auditory lists of large numbers (e.g., three ninety hundred two) when the numbers form a syntactically coherent structure allowing regrouping of the numbers in a single large number chunk (e.g., three hundred ninety two), although children of this age cannot yet count up to such large numbers.…”
Section: Discussionsupporting
confidence: 91%
“…One of the reasons for this gap may be that numbers have been considered as a block of verbal knowledge that, once acquired, is simply transferred to the corresponding numerical quantities. However, Barrouillet et al (2010) showed that children possess some implicit knowledge about two-or three-digit numbers in the counting list long before being able to recite them explicitly as when asked to count up to 1,000. The hypothesis that children would also possess some similar implicit knowledge about the first verbal numbers in the counting list (1-19) has never been empirically tested and validated by a detailed examination of the progressive elaboration of the verbal number sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative possibility, and the one we pursue here, is that young children extract regularities from their incidental experiences of written and spoken forms, and have ideas, perhaps imperfect, about how place value notation works. Consistent with this possibility, one previous study found that preschool children have better memory for well-formed multidigit numbers than non-wellformed numbers (Barrouillet, Thevenot, & Fayol, 2010). Formal instruction must build on or counter children's intuitive knowledge about place value, and thus a description of this early knowledge is a critical open question.…”
mentioning
confidence: 87%
“…A second study used a similar grammaticality manipulation: Barrouillet et al (2010) asked 5year old children to repeat sequences of number words, and compared their accuracy in fullygrammatical sequences (e.g., thirty two thousand seven hundred five) versus fragmented sequences (two seven five thirty hundred thousand). The children remembered more words in the grammatical sequences than in the fragmented ones.…”
Section: Existing Investigations Of Deep Syntactic Representation Of Numbersmentioning
confidence: 99%
“…For example, if the grammatical condition included the sequence "thirty two", the fragmented condition would include a sequence with the same words in different order -"two thirty". Similar to Barrouillet et al (2010), we always had a grammatical condition, in which each sequence included one or two grammatical segments (e.g., two hundred thirty four), and a fragmented condition, in which the sequence was broken into several grammatical segments (four two thirty hundred). Experiments 1 and 2 also included intermediate conditions, in which the sequence was partially fragmented (e.g., thirty four two hundred).…”
Section: The Present Studymentioning
confidence: 99%